High-Performance Work Systems in the Indonesian Context: A Strategic Human Resource Management Literature Review - Maryam Bte Badrul Munir; Umi Hamidaton Soffian Lee; Nur Hidayati Sanusi; Tahani Badrul Munir (GERASI INSAN NUSANTARA, 2026)
Over the past three decades, High-Performance Work Systems (HPWS) have become central to Strategic Human Resource Management (SHRM) globally. However, recent literature between 2020 and 2027 exhibits extreme geographical and disciplinary imbalances. While global outputs reached 32,467 documents—heavily dominated by China and the United States—a severe disciplinary indexing overlap exists with the hard sciences. More critically, a systematic filtering combining the core construct with the geographical boundary of Indonesia yielded a mere five empirical articles. A synthesis of these localized studies reveals that HPWS does not operate through direct effects; instead, its efficacy is fully contingent upon complex intervening mechanisms, such as psychological empowerment, emotional exhaustion, and organizational climate. This severe literature scarcity exposes a profound empirical gap, strongly validating the academic necessity for qualitative, context-specific investigations to bridge the regional SHRM theoretical divide within the unique Indonesian institutional landscape.